2009
DOI: 10.1007/s10571-009-9480-5
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Induces Hypophosphorylation of Intermediate Filaments and Reorganization of Actin Cytoskeleton in C6 Glioma Cells

Abstract: In this study, we investigated the actions of high homocysteine (Hcy) levels (100 and 500 microM) on the cytoskeleton of C6 glioma cells. Results showed that the predominant cytoskeletal response was massive formation of actin-containing filopodia at the cell surface that could be related with Cdc42 activation and increased vinculin immunocontent. In cells treated with 100 microM Hcy, folic acid, trolox, and ascorbic acid, totally prevented filopodia formation, while filopodia induced by 500 microM Hcy were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…** P \ 0.01, *** P \ 0.001 compared with each kinase subunit control; # P \ 0.05, ## P \ 0.01, ### P \ 0.001 compared with each kinase subunit HMG Neurotox Res an effective scavenger of peroxyl radicals, normalized the reduction of protein kinases and the phosphorylating levels of IF provoked by HMG, suggest that lipid peroxidation induced these effects. This is in accordance with the previously reported modulation of the cytoskeleton in conditions of redox imbalance in different cell types and under stress conditions (Loureiro et al 2010a(Loureiro et al , b, 2013Zamoner et al 2008a, b).…”
Section: Discussionsupporting
confidence: 93%
“…** P \ 0.01, *** P \ 0.001 compared with each kinase subunit control; # P \ 0.05, ## P \ 0.01, ### P \ 0.001 compared with each kinase subunit HMG Neurotox Res an effective scavenger of peroxyl radicals, normalized the reduction of protein kinases and the phosphorylating levels of IF provoked by HMG, suggest that lipid peroxidation induced these effects. This is in accordance with the previously reported modulation of the cytoskeleton in conditions of redox imbalance in different cell types and under stress conditions (Loureiro et al 2010a(Loureiro et al , b, 2013Zamoner et al 2008a, b).…”
Section: Discussionsupporting
confidence: 93%
“…That might be owing to the limited FRs expression on C6 cells. 4 In the competition assay, the uorescence intensity of cells incubated with G4-FA-PEG/DOX was reduced aer presaturation with free FA (62.44 for B2), illustrating that the decreased cellular uptake of G4-FA-PEG/DOX was due to the competitively binding of free FA with FRs on the C6 cell, [42][43][44] which further conrmed the targeting effect of FA to C6 cells through FRmediated endocytosis.…”
Section: Cellular Uptake Of Doxmentioning
confidence: 99%
“…We have previously demonstrated that the low stoichiometry of IF phosphorylation under basal conditions increases about 30% in rat brain slices exposed to toxic levels of metabolites , or toxins. ,, Conversely, hypophosphorylation has also been observed, reflecting misregulation of the phosphorylating system in response to different signals. In this context, different concentrations of (PhTe) 2 , from 5 to 100 μM, induced hypophosphorylation of GFAP and NF subunits mediated by activation of protein phosphatase 1 (PP1) in cerebral cortex of 9 and 15 day-old animals . Also, intracellular Ca 2+ levels were identified to be upstream of the signaling pathways targeting the cytoskeleton.…”
Section: Introductionmentioning
confidence: 97%